Kalibo during the Japanese occupation. - Ycay, Jesus L (1981.)
This study attempts to describe the economic, political and socio-cultural condition in Kalibo during the Japanese occupation. It will also include the conditions in the town before and after the Japanese occupation so as to provide a basis for comparison and to evaluate the effects of the Japanese occupation in Kalibo. Moreover , this study seeks to describe the manner by which Kalibo was captured by the Japanese, the resistance movement against them and the liberation of Kalibo., Before the Japanese arrived, Kalibo was a peaceful town. It was chiefly an agricultural town. The town was headed by a Municipal Mayor who was elected together with the Vice-mayor and the Councilors by the people. Education was limited to the elementary and the high schools levels only. Normalcy in the life was equated with simplicity and peace and order. Life in the Kalibo during the Japanese occupation was hard and disorderly. Fear, chaos and destruction left the Kalibonhons in the midst trauma despite some accounts of cordial treatment of the natives by some Japanese soldiers. Life was even more difficult after the war. But the Kalibonhons were happy and felt relieved because the war was over. They tried to make use of whatever was left of their belongings and started life anew. The effects of war motivated the people to strive harder to improve and develop the town of Kalibo and rebuild their own lives as well.
Thesis (Undergraduate, Bachelor of Arts in History) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Kalibo -- Japanese Occupation